2007
DOI: 10.1016/j.ejogrb.2005.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding in the umbilical cord in altered glycemia

Abstract: Objective: Content and distribution of the oligosaccharides in the umbilical cord from pregnancies with altered glycemia were investigated. Study design: A prospective cohort study was conducted in the Florence Policlinic of Careggi, Italy. Samples of cord from physiological pregnancies (n = 20), from pregnancies with minor degree of glucose intolerance (n = 20) and from pregnancies with gestational diabetes mellitus (GDM) treated with insulin (n = 20) were collected. Eleven lectins were used (ConA, WGA, PNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Importantly, this conclusion is also supported from studies comparing patterns of lectin binding in human tissues under healthy and diseased states. Examination of lectin binding to umbilical cords demonstrated increased ConA and UEA binding to the vein compared with the artery and lectinbinding patterns during pregnancy complications are altered in both pattern and intensity within the vasculature (Sgambati et al 2003(Sgambati et al , 2007. Our own studies have shown that there Scott et al (2012).…”
Section: Lectin-binding Patterns Vary Between Vascular Bedsmentioning
confidence: 74%
“…Importantly, this conclusion is also supported from studies comparing patterns of lectin binding in human tissues under healthy and diseased states. Examination of lectin binding to umbilical cords demonstrated increased ConA and UEA binding to the vein compared with the artery and lectinbinding patterns during pregnancy complications are altered in both pattern and intensity within the vasculature (Sgambati et al 2003(Sgambati et al , 2007. Our own studies have shown that there Scott et al (2012).…”
Section: Lectin-binding Patterns Vary Between Vascular Bedsmentioning
confidence: 74%